EVALUATING AND DEVELOPING TEXTBOOK FOR TRANSLATION CLASS BASED ON STUDENTS’ SATISFACTION AND NEED ANALYSIS - Helena M. A Rijoly (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2023)
University Course Textbook or “Buku Ajar” is a handbook for a specific course/subject/class written by the lecturer of that course in accordance with the curriculum and syllabus of the course. The textbook is a crucial addition to support the teaching and learning process in the classroom. A good textbook will provide the users (lecturers and students) a one-stop place for lesson, exercises and practices. A good textbook will motivate students to learn, enable students to follow the flow of learning, and allowing an opportunity for elaboration. Translation class at English Education Study program had been using the same textbook since 2014. Thus, it was time to revise and improve the textbook according to the changing curriculum from KKNI to Merdeka Belajar Curriculum. This research was conducted in Translation Class in 2020 and 2021. In 2020, students were asked to evaluate the 2014 textbook to obtain students feedback for the improvement. In 2021 a new revised textbook was completed and used in the class. The students were later asked for their feedback and evaluation of the new textbook. The instrument used was an online questionnaire with close-ended and open-ended items. It was divided into 3 Assessment Aspects: Textbook Content and Face Evaluation, Classroom Activity Experience and Feedback from students. The result shows that 2014 textbook received an overall low satisfaction and feedback. The new and revised textbook that was developed based on these feedback and evaluation received an overwhelmingly positive feedback and high satisfaction rate on all aspects.